Analysis of Corn Farming and Its Contribution to Family Income in Palipi Village, Palipi District, Samosir Regency - Sitohang, Maryanti; Saragi, Cyprianus P H; Nainggolan, Mariani (Jurnal Teknologi dan Ilmu Pertanian, 2025)
This study aims to (1) determine the amount of production spent by farmers to manage corn farming per hectare/planting season in Palipi Village, Palipi District, Samosir Regency, (2) determine the amount of net income obtained from corn farming per hectare/planting season in Palipi Village, Palipi District, Samosir Regency, and (3) determine the contribution of net income from corn farming to family income. The research area was determined using purposive sampling. The research data is primary data with a sample size of 34 determined using the accidental sampling method. The results show that the average production cost is Rp14,216,693.63/ha/planting season, the average net income is Rp7,383,306.37/ha/planting season, and the contribution of corn farmer income to total family income in the research area is 70.80%. This contribution of corn farming income is considered high (>50%).